2000
DOI: 10.1165/ajrcmb.23.5.3921
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Activates Jun-N-Terminal Kinase, Extracellular Signal–Regulated Protein Kinase, and p38 Kinase in Pulmonary Arteries

Abstract: Chronic alveolar hypoxia is the major cause of pulmonary hypertension. The cellular mechanisms involved in hypoxia- induced pulmonary arterial remodeling are still poorly understood. Mitogen-activated protein kinase (MAPK) is a key enzyme in the signaling pathway leading to cellular growth and proliferation. The purpose of this investigation was to determine the roles that MAPKs, specifically Jun-N-terminal kinase (JNK), extracellular signal-regulated protein kinase (ERK), and p38 kinase, play in the hypoxia-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 28 publications
8
72
1
Order By: Relevance
“…We also observed elevations in p42/44 MAPK in IL-13R␣1 Ϫ/Ϫ and IL-13R␣2 Ϫ/Ϫ mice compared with wild-type mice, independent of S. mansoni infection, and thus the contribution of p42/44 MAPK to PH in this model is unclear. Indeed, prior studies have shown increased expression of p42/44 MAPK in rats exposed to chronic hypoxia, 49 but which may not be necessary for the hypertensive response. 50 Abnormal TGF-␤ family signaling has been linked to human and experimental PAH.…”
Section: Discussionmentioning
confidence: 96%
“…We also observed elevations in p42/44 MAPK in IL-13R␣1 Ϫ/Ϫ and IL-13R␣2 Ϫ/Ϫ mice compared with wild-type mice, independent of S. mansoni infection, and thus the contribution of p42/44 MAPK to PH in this model is unclear. Indeed, prior studies have shown increased expression of p42/44 MAPK in rats exposed to chronic hypoxia, 49 but which may not be necessary for the hypertensive response. 50 Abnormal TGF-␤ family signaling has been linked to human and experimental PAH.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, both flt-1 and iNOS are known HIF-1␣ target genes in endothelial cells, yet our preliminary data (not shown) suggest that these genes are not up-regulated in the K14-HIF-1␣⌬ODD transgenic mice. Moreover, hypoxia itself may induce additional cytokine expression or recruit other master regulatory transcription factors within specific cell types, such as Egr-1 up-regulation in hypoxic endothelium (Jin et al 2000), that may mediate blood vessel permeability alone or combined with HIF-1␣ stabilization. Additional modulators of permeability may also exist in vessels in hypoxic wounds and tumors, which are known to be leaky (for review, see Carmeliet and Jain 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that H 2 O 2 stimulated tyrosine kinase activity and caused receptor tyrosine phosphorylation, suggesting that H 2 O 2 -induced mitogenic response is, in part, mediated through platelet-derived growth factor receptor in aortic smooth muscle cells (Jin et al, 2000). Among two classic tyrosine kinases, receptor and nonreceptor tyrosine kinases, receptor tyrosine kinases virtually are the growth factor receptors located in the inner side of the cytoplasmic membrane and subjected to dimerization and autophosphorylation upon activation.…”
Section: Growth Factor Receptor and Metal-catalyzed Free Radical Formmentioning
confidence: 99%